Utilization of Academic Applications to Support the Education Administration System at the Academic Hospital of Gadjah Mada University - Nurwestu Rusetiyanti; Domas Fitria Widyasar; Yusuf Afandi; Anindita Mahitala; Agung Supoyo (Green Publisher Indonesia, 2026)
Digitalization in academic hospital settings is essential to improve the efficiency and quality of educational administrative services. Teaching hospitals face challenges in developing innovative, user-friendly, and efficient systems that can support clinical education processes. In response to this need, the Academic Hospital of Gadjah Mada University (RSA UGM) developed a mobile-based application called “Akademik” to facilitate student registration and administrative processes. This research aims to evaluate the utilization of the “Akademik” application in supporting the educational administration system at RSA UGM. A descriptive quantitative method was used, with simple random sampling involving 47 respondents. Data were collected through questionnaires and analyzed using descriptive statistics with SPSS. The results show that 95.7% of respondents stated that the application instructions were clear and easy to understand, 95.7% perceived the application as easy to use, 89.4% expressed satisfaction with the application, and 87.2% reported that the student registration process became faster. These findings indicate that the “Akademik” application contributes positively to improving administrative efficiency and user experience. In conclusion, the “Akademik” application effectively enhances the educational administration process at RSA UGM by making it more efficient, user-friendly, and environmentally sustainable through reduced paper usage. However, continuous system development and integration are necessary to further optimize its performance and support the broader clinical education system.